EFFORTS OF ARABIC LANGUAGE TEACHERS TO ENCOURAGE STUDENTS' INTEREST IN LEARNING ARABIC - Juwairiyah Siregar; Adamu Abubakar Muhammad (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study aimed to describe students’ interest, teachers’ efforts to increase student interest, and the difficulties teachers face in enhancing interest in learning Arabic. A descriptive qualitative method was used. The results indicated that students' interest in learning Arabic was high. Efforts by Arabic teachers to boost this interest included convincing students of the importance of Arabic lessons in their lives, encouraging participation, helping students understand the material, fostering positive relationships, and using various teaching methods. The challenges teachers encountered were student laziness, large class sizes, and the lack of textbooks for some students, which led to students’ inattentiveness. Overall, it was found that teachers had made various commendable efforts to increase students’ interest in learning Arabic.